Fun and Games AT Malory Towers - Cox, Pamela (London, Egmont Children's Books, 2015)
New girl Millicent clashes with the feisty June over the school's priorities: a music concert or tennis tournament? But both pale into insignificance when it's found there's a thief in the fifth form.
A1 Fiction shelf
Keywords: English fiction story